PENDEKATAN KONSTRUKTIVISME DI MALAYSIA DAN BRUNEI DARUSSALAM: SATU TINJAUAN AWAL TERHADAP PENGALAMAN GURU PENDIDIKAN ISLAM: CONSTRUCTIVISM APPROACH IN MALAYSIA AND BRUNEI DARUSSALAM: A PRELIMINARY STUDY ON ISLAMIC EDUCATION TEACHERS’ EXPERIENCES - Tengku Kasim, Tengku Sarina Aini; Abdurajak, Fatimah Sahida; Md Yusoff, Yusmini; Baharuddin, Madiha (Journal of Islamic Educational Research, 2017)
The formulation of the education system in the form of using constructivist approach is not new, however, it seems difficult to apply within Asean countries, which accustom to the traditional approach. National education system in Malaysia and Brunei Darussalam has derived various initiatives to support the constructivism approach. Malaysia has introduced a new secondary school curriculum, Secondary School Standard Curriculum (SSSC) to replace the Integrated Secondary School Curriculum. While in Brunei Darussalam also introduced the National Education System of the 21st Century (SPN21). Due to this issue, this study was conducted to analyze the constructivist approach in both education curriculum. Qualitative research has been applied to identify the implementation of the constructivist approach in teaching Islamic Education. In addition, documentation method and semi-structured interviews were conducted with two informants, who is a novice teacher from Malaysia and an experienced teacher from Brunei Darussalam. Consequently, this article discusses several data of the study that will be faced by teachers or educators upon its implications by implementing constructivist approach in Islamic Education subject in Malaysia and Brunei Darussalam.